2017
DOI: 10.1038/s41598-017-14154-w
|View full text |Cite
|
Sign up to set email alerts
|

The recovery status from delayed graft function can predict long-term outcome after deceased donor kidney transplantation

Abstract: The effect of delayed graft function (DGF) recovery on long-term graft outcome is unclear. The aim of this study was to examine the association of DGF recovery status with long-term outcome. We analyzed 385 recipients who underwent single kidney transplantation from brain-dead donors between 2004 and 2015. Patients were grouped according to renal function at 1 month post-transplantation: control (without DGF); recovered DGF (glomerular filtration rate [GFR] ≥ 30 mL/min/1.73 m2); and incompletely recovered DGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…Contrariwise, those with uncomplete recovery presented lower survival and lower GFR at five years after transplantation. 23…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, those with uncomplete recovery presented lower survival and lower GFR at five years after transplantation. 23…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that DGF alone can influence long-term outcomes, including decreased graft and patient survival. [21][22][23] Although acute tubular necrosis is the most frequent cause of DGF, endothelial injury and microvascular dysfunction also play an important role in DGF pathogenesis. 6 Elevation in sFlt-1 levels simultaneously with DGF occurrence may argue for a short-term effect of sFlt-1 on the microvascular endothelium, resulting in acute hemodynamic changes, 24,25 followed by a long-term impairment in endothelial repair and subsequent vessel dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, not DGF per se but rather ability to recover from DGF as indicated, e.g., by GFR at 1 month might be a more reliable marker of long-term graft outcome and quality, as recently reported by Lee et al (76). Donor age, donor final creatinine and cold ischemia time were significantly associated with DGF recovery status (76).…”
Section: Critical Discussion Of Surrogate Markers Used For Kidney Quamentioning
confidence: 75%